Upaya Pemberdayaan Kader dan Ibu Hamil tentang Senam Hamil untuk Mengatasi Ketidaknyamanan Kehamilan pada Ibu Hamil di Posyandu Kinasih Banjarsari Surakarta - Maharani Pratiwi, Ajeng; Prastyoningsih, Aris; Ani Noor, Frieda; Sopiah Suryani, Iis (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2024)
Pregnancy exercise is a form of structured exercise or exercise. Exercising on a regular basis will improve blood circulation, strengthen muscles and flex joints and can reduce common disorders during pregnancy such as aches, back pain, muscle stiffness, constipation, and reduce leg swelling. Doing pregnancy exercise regularly can reduce lower back pain, one of which is by kneeling, rotating the pelvic bones, bending the buttocks, bending the knees, chest. The purpose of this community service is that after receiving counseling it is hoped that pregnant women and Health Cadres members of Posyandu Kinasih, Banjarsari Subdistrict, Surakarta can apply and be able to provide education to pregnant women to carry out pregnancy exercise to overcome discomfort in pregnant women. The target of counseling activities about pregnancy exercise is all Health Cadres and pregnant women in the Banjarsari Village, Surakarta. The expected output of pregnancy exercise counseling activities for cadres and members of the Balita Kinasih Posyandu in Banjarsari Surakarta Village is an increase in knowledge and skills about pregnancy exercise for mothers and cadres. The results of community service are that after counseling cadres and pregnant women become more knowledgeable, understand about pregnancy exercise as evidenced in the results of the evaluation through the distribution of questionnaires, the average value of the level of knowledge is from 70% to 90%. Based on the implementation of community service, it can be concluded that there is an increase.